On the origins of diastereoselectivity in the alkylation of diketopiperazine enolates - Bull, S; Davies, S; Garner, A; Parkes, A; Roberts, P; Sellers, T; Smith, A; Tamayo, J; Thomson, J; Vickers, R (2007)
High levels of diastereoselectivity are observed for benzylation of the lithium enolates of (S)-N,N′-bis-para-methoxybenzyl-3-iso-propyl- piperazine-2,5-dione, (S)-N(1)-para-methoxybenzyl-N(4)-methyl-3-iso-propyl- piperazine-2,5-dione and (S)-N(1)-methyl-N(4)-para-methoxybenzyl-3-iso-propyl- piperazine-2,5-dione. These data suggest that the high diastereofacial selectivity observed for alkylation of these diketopiperazine templates is mainly a consequence of the relay of stereochemical information from C(3) to C(6) via the influence of 1,2-torsional strain introduced by the N-alkyl substituents, rather than through minimisation of steric interactions alone. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.